Global poverty dynamics and resilience building for sustainable poverty reduction - Li, Yuheng; Wu, Wenhao; Wang, Yongsheng (Journal of geographical sciences, 2021)
There is less than a decade left to accomplish the goal of ending global poverty by 2030. This paper investigates global poverty dynamics and finds a shift in the world’s poverty gravity center from South Asia to Africa in the period 1990–2015. Sub-Saharan Africa has become the main battlefield for poverty reduction in the world. Global poverty reduction has been accompanied by political instability and local conflicts, economic marginalization, rural decline, and natural hazards as well as climate change which are jointly impacting the least developed areas and making the world’s poverty reduction vulnerable to external shocks. The “STAR” scheme, including maintaining political stability, promoting targeted poverty alleviation, implementing regular assessments of poverty reduction initiatives, and revitalizing rural and poverty-stricken areas, is proposed with specific measures to enhance the resilience capacity of poverty alleviation in the world.